2017
DOI: 10.7869/tg.404
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous drainage may not be necessary in a significant subset of patients with complicated liver abscess

Abstract: Background: Clinical features and outcomes of liver abscess are ever changing, even in South Asia, where parasitic infections are common. It is important to devise management strategies to suit the changing needs. We wanted to capture this emerging spectrum in "real life" through assessment of clinical features, management strategies and outcomes of a cohort of treated liver abscess patients at a single center. Methods: A retrospective study of patients admitted to a referral institution between February 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(12 reference statements)
2
1
0
Order By: Relevance
“…Twenty four (24%) and 62 (62%) patients were occasional and frequent drinkers while 14 (14%) patients did not drink alcohol. This is comparable to the studies of Choudhary et al and Saptarshi et al 15,18 Choudhary et al study identified the clinical profile of liver abscess reported alcohol was the single most consistent etiological factor in 84% patients of liver abscess. 19 Saptarshi et al study reported possible risk factors identified were alcohol use in 36 (23.4 %) patients, biliary obstruction in 32 (20.8%) and diabetes in 17 (11%) patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Twenty four (24%) and 62 (62%) patients were occasional and frequent drinkers while 14 (14%) patients did not drink alcohol. This is comparable to the studies of Choudhary et al and Saptarshi et al 15,18 Choudhary et al study identified the clinical profile of liver abscess reported alcohol was the single most consistent etiological factor in 84% patients of liver abscess. 19 Saptarshi et al study reported possible risk factors identified were alcohol use in 36 (23.4 %) patients, biliary obstruction in 32 (20.8%) and diabetes in 17 (11%) patients.…”
Section: Discussionsupporting
confidence: 89%
“…17 In the present study, 4 (4%) patients died while 96 (96%) patients survived; 3 (3%) patients had undergone surgery while 1 (1%) patient was percutaneously drained. This is comparable to the studies of Saptarshi et al and Jha et al 17,18 Saptarshi et al, study reported surgical intervention in 2 (1.30%) patients. Mortality rates among liver abscess patients stood at 3.9%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation